PEMBANGUNAN CITRA ABURIZAL BAKRIE DI MEDIA SOSIAL TWITTER STUDI EVALIATIF TERHADAP BAKAL CALON PRESIDEN INDONESIA 2014 - Bayu Saputra; Belli Nasution (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Twitter is a social media that allows users to send and read messages called tweets (chirp), the tweets are text messages are limited to 140 characters displayed on the user profile page. Due to its extensive use and fast, becoming a social media to spread the ideas and thoughts concerning the political and social issues lately. Twitter now has developed also as a means of political campaigns and self-image, on political campaigns conducted by the political elite in social media is a form of political communication as a political activity. This study aims to (1) To determine how the image-building efforts Bakrie as candidates President on Twitter (2) to determine how student opinion of Communication Studies at the imaging Fisipol Unri Bakrie at Twitter.In this research authors used qualitative research methods with the presentation of descriptive analysis. Data collection techniques based on observation, interviews and documentation. Informants in this study were 8 people taken by purposive technique. This study uses a model of image formation and Ardianto Soemirat, by using a technique that checks the validity of the data through the extension of participation and triangulation.The results of this study indicate Bakrie use Twitter as a medium of spreading information on the activities done during January and February 2014. Bakrie regularly informed about the activities themselves in activities visit and provide assistance to flood victims in Jakarta also social events and roadshow in a number of cities in Indonesia. Through tweets related to flooding in Jakarta and roadshow, it appears that the Bakrie seeks to provide information about the activities and concerns. Bakrie tweets activity seeks to build its image, Bakrie tried to explain to the audience that he was concerned with the victims of the floods that hit Jakarta, Bakrie wants to show that he took to the location to be able to directly provide assistance. Bakrie also held a number of roadshow events in several cities in Indonesia.Keyword : Image Development, Bakrie, Twitter